(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
This paper analysed passengers’ traffic of the Abuja-Kaduna train service (AKTS). The AKTS is gaining recognition and increasing patronage of high-profile individuals, private car owners, and other passengers plying the Abuja-Kaduna road for various reasons (Suleiman, 2023; Suleiman, 2021). Data used for this study was obtained through both primary and secondary sources of data. The primary data involved the administration of 45 questionnaires to the railway staff in charge of the AKTS operation. While secondary data was obtained from the Nigerian Railway Corporation (NRC). The secondary data cover operational data for passengers transported by the AKTS between 2016-2021. The study employed the use of both descriptive and inferential statistical methods of data analysis. The findings of the descriptive analysis revealed that 2019 recorded the highest passengers traffic, while 2016 recorded the lowest. As for monthly traffic, December recorded the highest while May recorded the lowest. The result of one-way between-groups analysis revealed that there was a statistically significant difference at the p < .05 level in the yearly traffic.